Problematika Kualitas Imam Pada Masjid Bakti Desa Bailangu Kec. Sekayu Kab. Musi Banyuasin - Lesti Febrianti; Anang Walian (Berkala Ilmiah Pendidikan, 2024)
This research is entitled “Promblematics of Imam Quality at the Bakti Mosque in Bailangu Village, District. Sekayu District Musi Banyuasin”. This research was motivated by a phenomenon resulting from previous research which concluded that there was a lack of quality of imams at the Bakti mosque in Bailangu Village. The aim of this research is to find out the factors that influence the quality of the imam and how the mosque management attempts to improve the quality of the imam at the Bakti Mosque in Bailangu Village. The approach used in this research is a qualitative method with a descriptive approach. The data collection techniques include observation, interviews and documentation techniques using primary and secondary data sources. Meanwhile, the data analysis techniques used are data reduction, data presentation and drawing conclusions. Based on the research results, there is still a lack of quality priests at the Bakti Mosque in Dailangu Village, District. Sekayu District Musi Banyuasin, which is caused by several factors that influence the quality of priests in the form of reliability, responsiveness, assurance, empathy and physical evidence. Apart from that, there are efforts by the mosque management to improve the quality of imams at the Bakti Mosque in Bailangu Village in the form of holding training and professional development programs for imams. As well as providing assistance or mentoring by mosque administrators or senior imams to new imams in addition to ensuring adequate facilities and means to support the implementation of worship.